Cognitive ability and education: How behavioural genetic research has advanced our knowledge and understanding of their association. (April 2020) - Malanchini, Margherita; Rimfeld, Kaili; Allegrini, Andrea G.; Ritchie, Stuart J.; Plomin, Robert
Highlights: Starting from middle childhood, studies point to a strong genetic basis in the association between cognitive ability and academic performance. Over development, genetic influences are amplified by environmental experiences trhigh gene-environment interplay. The strong stability and heritability of academic performance is not driven entirely by cognitive ability. Other educationally-relevant noncognitive characteristics contribute to accounting for the genetic variation in academic performance beyond cognitive ability. Overall, genetic research has provided compelling evidence that has resulted in greatly advancing our knowledge and understanding of the association between cognitive ability and learning. Considering both cognitive and noncognitive skills as well as their biological and environmental underpinnings will be fundamental in moving towards a comprehensive, evidence-based model of education. Abstract: Cognitive ability and educational success predict positive outcomes across the lifespan, from higher earnings to better health and longevity. The shared positive outcomes associated with cognitive ability and education are emblematic of the strong interconnections between them. Part of the observed associations between cognitive ability and education, as well as their links with wealth, morbidity and mortality, are rooted in genetic variation. The current review evaluates the contribution of decades of behavioural genetic research to our knowledge and understanding of the biological and environmental basis of the association between cognitive ability and education. The evidence reviewed points to a strong genetic basis in their association, observed from middle childhood to old age, which is amplified by environmental experiences. In addition, the strong stability and heritability of educational success are not driven entirely by cognitive ability. This highlights the contribution of other educationally relevant noncognitive characteristics. Considering both cognitive and noncognitive skills as well as their biological and environmental underpinnings will be fundamental in moving towards a comprehensive, evidence-based model of education.